2023
DOI: 10.1002/adhm.202302881
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh‐Efficacy VEGF Neutralization Using Carbonized Nanodonuts: Implications for Intraocular Anti‐Angiogenic Therapy

Hong‐Jyuan Jian,
Anisha Anand,
Jui‐Yang Lai
et al.

Abstract: Ocular angiogenesis, associated with diseases such as retinopathy of prematurity and diabetic retinopathy, is a leading cause of irreversible vision loss. Herein, carbon nanodonuts (CNDs) with a donut‐shaped structure are synthesized using sodium alginate (SA) and 1,8‐diaminooctane (DAO) through a one‐step thermal process. The formation of SA/DAO‐CNDs occurs through a crosslinking reaction between SA and DAO, creating amide bonds followed by partial carbonization. In human retinal pigment epithelial cells expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…27 There have been a few reports on the application of nanozyme in the eyes. [28][29][30][31] The small particle size of nanozyme enhances their ability to penetrate tissues, thereby improving drug permeability in ocular settings. 32 It has been reported that many carbon nanomaterials can act as electron donors or acceptors, endowing them as pro-oxidants or antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…27 There have been a few reports on the application of nanozyme in the eyes. [28][29][30][31] The small particle size of nanozyme enhances their ability to penetrate tissues, thereby improving drug permeability in ocular settings. 32 It has been reported that many carbon nanomaterials can act as electron donors or acceptors, endowing them as pro-oxidants or antioxidants.…”
Section: Introductionmentioning
confidence: 99%